Hepatic Fibrosis Is Universal Following Fontan Operation, and Severity is Associated With Time From Surgery: A Liver Biopsy and Hemodynamic Study. Issue 5 (26th April 2017) - Goldberg, David J.; Surrey, Lea F.; Glatz, Andrew C.; Dodds, Kathryn; O'Byrne, Michael L.; Lin, Henry C.; Fogel, Mark; Rome, Jonathan J.; Rand, Elizabeth B.; Russo, Pierre; Rychik, Jack
Abstract : Background: Congestive hepatopathy is a recognized complication of Fontan physiology. Data regarding the incidence of hepatopathy and risk factors are lacking. Methods and Results: Liver biopsies and cardiac catherizations were performed as part of an evaluation offered to all patients ≥10 years after Fontan. Quantitative determination of hepatic fibrosis was performed using Sirius red staining with automated calculation of collagen deposition per slide (%CD). Biopsies from included subjects were compared to stained specimens from controls without known fibrotic liver disease. Patient characteristics, echocardiographic findings, and hemodynamic measures were evaluated as potential risk factors. The cohort consisted of 67 patients (31 female) at mean age of 17.3±4.5 years and mean time from Fontan of 14.9±4.5 years. Right ventricular morphology was present in 37 subjects. Median %CD by Sirius red staining was 21.6% (range 8.7% to 49.4%) compared to 2.6% (range 2.2% to 3.0%) in controls. There was a significant correlation between time from Fontan and degree of Sirius red staining ( r =0.33, P <0.01). Serum liver enzymes and platelet count did not correlate with %CD. The median inferior vena cava pressure was 13 mm Hg (range 6‐24 mm Hg) and did not correlate with %CD. There was no difference in %CD based on ventricular morphology or severity of atrioventricular valve insufficiency. Conclusions: In this cohort of predominantly asymptomatic children and adolescents electively evaluated after a Fontan operation, all exhibited evidence for hepatic fibrosis as measured by collagen deposition in the liver. Time from Fontan was the only factor significantly associated with collagen deposition. These findings demonstrate that liver fibrosis is an inherent feature of Fontan physiology and that the degree of fibrosis increases over time.